Exposure to ambient air pollution and blood lipids in adults: The 33 Communities Chinese Health Study. (October 2018) - Yang, Bo-Yi; Bloom, Michael S.; Markevych, Iana; Qian, Zhengmin (Min); Vaughn, Michael G.; Cummings-Vaughn, Lenise A.; Li, Shanshan; Chen, Gongbo; Bowatte, Gayan; Perret, Jennifer L.; Dharmage, Shyamali C.; Heinrich, Joachim; et al.
Abstract: Background: Little information exists on the lipidemic effects of air pollution, particularly in developing countries. We aimed to investigate the associations of long-term exposure to ambient air pollutants with lipid levels and dyslipidemias in China. Methods: In 2009, a total of 15, 477 participants aged 18–74 years were recruited from the 33 Communities Chinese Health Study conducted in three Northeastern China cities. Total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) were measured in participants' blood specimens. Three year (2006–08) average air pollution concentrations were assessed using data from 33 communities (particles with diameters ≤1.0 μm (PM1 ) and ≤2.5 μm (PM2.5 ) were predicted using a spatial statistical model) or 11 air monitoring stations (particles with diameters ≤10 μm (PM10 ), sulfur dioxide (SO2 ), nitrogen dioxide (NO2 ), and ozone (O3 )). Associations were evaluated by two-level logistic and generalized linear regression models. Results: We detected many significant associations between exposure to air pollutants (especially for PM1 and PM2.5 ) and blood lipid levels. Most of the associations suggested deleterious effects on blood lipid markers (e.g., a 10 μg/m 3 increase in PM1 was associated with 1.6% (95% confidence interval (CI): 1.1, 2.0), 2.9% (95% CI: −3.3, 9.3), and 3.2% (95% CI: 2.6, 3.9) higher levels of TC, TG, and LDL-C, respectively, but 1.4% (95% CI: −1.8, −0.9) lower HDL-C levels), although beneficial associations were found for O3 . In analysis with dyslipidemias, all the observed associations suggested deleterious lipidemic effects of air pollutants, and no significant beneficial association was observed for O3 . Stratified analyses showed that the associations were stronger in overweight or obese participants; sex and age modified the associations, but the pattern of effects was mixed. Conclusions: Long-term ambient air pollution was associated with both altered lipid profiles and dyslipidemias, especially among overweight or obese participants. Highlights: Little information exists on the lipidemic effects of ambient air pollution. We conducted a cross-sectional study among 15, 477 Chinese adults. Associations between ambient air pollution and blood lipids were examined. Long-term ambient air pollution may have deleterious effects on lipid profiles.